2017
DOI: 10.1534/genetics.116.196493
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Population Genetics

Abstract: Molecular population genetics aims to explain genetic variation and molecular evolution from population genetics principles. The field was born 50 years ago with the first measures of genetic variation in allozyme loci, continued with the nucleotide sequencing era, and is currently in the era of population genomics. During this period, molecular population genetics has been revolutionized by progress in data acquisition and theoretical developments. The conceptual elegance of the neutral theory of molecular ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 344 publications
(440 reference statements)
1
109
0
Order By: Relevance
“…In heterogametic males (XY), X-linked mutations are hemizygous and therefore directly exposed to selection, whereas new recessive autosomal mutations are masked from expression in heterozygotes individuals. Moreover, the effective recombination rate is ~1.8-fold greater on the X compared to autosomes [194], which reduces Hill-Robertson interference and increases the efficiency of selection. The increased selection in hemizygous males together with the higher efficiency of selection due to the increased recombination may act synergistically to account for the "faster-X evolution", which is generally supported by genomic data collected in Drosophila populations (reviewed in [255]).…”
Section: Faster-x Evolutionmentioning
confidence: 99%
“…In heterogametic males (XY), X-linked mutations are hemizygous and therefore directly exposed to selection, whereas new recessive autosomal mutations are masked from expression in heterozygotes individuals. Moreover, the effective recombination rate is ~1.8-fold greater on the X compared to autosomes [194], which reduces Hill-Robertson interference and increases the efficiency of selection. The increased selection in hemizygous males together with the higher efficiency of selection due to the increased recombination may act synergistically to account for the "faster-X evolution", which is generally supported by genomic data collected in Drosophila populations (reviewed in [255]).…”
Section: Faster-x Evolutionmentioning
confidence: 99%
“…Some studies observed phylogeographic structure among P. microlepis populations (Koblmüller et al, 2009;Lee et al, 2010;Raffini et al, 2017); however, the effects of this population subdivision and demographic history on the phenotypic and genetic bases of head asymmetry have not been fully investigated. Neutral population processes such as mutation, gene flow and genetic drift can play an important role in phenotypic/genetic diversity and hence adaptation, especially for polygenic traits (reviewed in Hedrick, 2011;Yeaman, 2015;Bernatchez, 2016;Casillas & Barbadilla, 2017, examples in cichlids: Koblmüller et al, 2011Husemann, 2013;Sefc et al, 2017). Particularly, hybridization have a relevant impact on intra-and interspecific divergence (reviewed in Schwenk et al, 2008;Abbott et al, 2013), as seen in cichlids (e.g., Nichols et al, 2015;Kautt et al, 2016;Meier et al, 2017;Irissari et al, in press).…”
Section: Toward Coupling Phenotype and Genotypementioning
confidence: 99%
“…The dominant paradigm in population genetics is based on a comparison of observed data with parameters derived from a theoretical model [1,2]. Specifically for DNA sequences, many techniques have been developed to test for extreme relationships between average sequence diversity (number of DNA differences between individuals) and the number alleles (distinct DNA sequences in the population).…”
Section: Introductionmentioning
confidence: 99%